Phenolic Content, Flavonoid Content and Antioxidant Efficacy of Opuntia elatior Mill. - Kolar, Firdose R.; Kambhar, Sidanand V.; Kamble, Vaishali S.; Lamani, Babu R. (Free Radicals and Antioxidants)
Background: The current study aims at examining the unripened and ripened fruits of Opuntia elatior Mill. for its phytochemical constituents and antioxidant potential. Materials and Methods: The extracts of unripened and ripened fruits of O. elatior were prepared using various solvent systems (aqueous, ethanol, methanol, and acetone) and the extracts were evaluated for phenolics and flavonoid content as well as antioxidant activity. The antioxidant activity of the extracts was assessed by using Ferric reducing antioxidant power assay, ferrous ion chelating activity, phosphomolybdenum reducing power assay and hydroxyl radical scavenging assay. Results: The results of the study revealed that among the unripened and ripened fruits of O. elatior analyzed, unripened fruits yielded highest content of phenolics and flavonoids as compared to ripened fruits at fresh weight as well as dry weight basis. The extracts were also found to have significantly different levels of antioxidant activities in different antioxidant methods. The antioxidant activity varied in ripened and unripened fruits as well as among the solvents in different assays. The overall results indicated that the dried fruits of O. elatior having highest amount of phenolics and flavonoids also exhibited highest antioxidant activity as compared to fresh fruits. Significantly, a positive correlation was observed between the phytochemical compounds and antioxidant activity. Conclusion: The study specified that dried fruits of O. elatior showed highest phenolics and flavonoid content as well as highest antioxidant activity. Thus, dried fruits of O. elatior can be used as an accessible source of natural antioxidants with consequent health benefits.
Keywords: Opuntia; Cactaceae; Phenolics; Flavonoids; Free Radicals; Antioxidants